Comparative biochemical characterization of Drosophila Melanogaster epsilon class glutathione s-transferase, DmGSTE6 and DmGSTE7 / Vennobaahshini a/p Venu - Venu, Vennobaahshini (2015)

(untitled)
The study compares the biochemical behavior of two epsilon class Glutathione S- Transferase (GSTs) genes from Drosophila melanogaster, namely gste6 and gste7. Both GSTs were cloned, expressed and homogenously purified using a combination of anionic exchange chromatography and GSH-affinity matrix. Bioinformatics analysis indicated that both shared 83% and 69% amino acid sequence similarity and identity respectively. Each GSTE6 shared 79% and 77% similarity and GSTE7 has 77% similarity towards GST6A and GST6B of Musca domestica, respectively which are known to participate in resistance towards insecticides. The expressed recombinant proteins were tested for their activity towards 12 model substrates. Based on the pattern of activity toward these substrates, these GST isozymes exhibited overlapping but similar substrate specificities. The isozymes were only active towards 1-chloro-2, 4-dinitrobenzene (CDNB), 1, 2-dichloro-4-nitrobenzene (DCNB) and p-nitrobenzyl chloride (p-NBC). GSTE6 possesses greater catalytic efficiency (Kcat/Km) towards substrate CDNB but GSTE7 possesses greater catalytic efficiency (Kcat/Km) towards substrate DCNB and p-NBC. Thin layer chromatography analysis showed the isozymes were not able to conjugate 13 tested insecticides. The inhibition kinetics of natural products and dyes towards both GSTs in- vitro revealed that phenol red dye possessed inhibition effects only on GSTE6 while rose bengal and cardiogreen dye inhibit excellently both GSTE6 and GSTE7. Interestingly, methylene blue dye and trans-chalcone have been showed to stimulate GSTE7 activity towards CDNB.